UJI BIOAKTIVITAS ANTIBAKTERI TANAMAN OBAT TRADISIONAL - Merdana, I Made (Buletin Veteriner Udayana, 2012)
The research has been conducted to five kinds of traditional herbs which were collectedfrom Tajun village, Kubutambahan District, Buleleng Regency, Bali. It was conductedthrough extracting process and antibacterial bioactivity test to the five traditional herbs,naely kamboja (Plumeria rubra), kedondong (Spondias pinnata), kembang sepatu(Hibiscus rosa sinensis), mangga (Mangifera indica) dan manggis (Garnicia mangostana).The bioactivities antibaterial of these herbs had been exsperimented toward Micrococcusluteus and Escherichia coli. As the result, the leaves of the herbs which actively hamperedthe growth of Micrococcus luteus and Eschericia coli bacteria was manggis leaves (Garnicia mangostana). The herb which only hampered the growth ofEscherichiacoli actively was kamboja leaves (Plumeria rubra), kembang sepatu (Hibiscus rosasinensis), mangga (Mangifera indica). Mean while kedongdong leaves do not haveactivities to both kins of bacteria. Manggis had a goods potential to hamper the growthof Micrococcus luteus and Eschericia coli. It could be seen from the wide area of obstacleproduced by manggis leaves (Garnicia mangostana), namely 4,63 mm2 towardMicrococusluteus and toward Eschericia coli 5,63 mm2 in 105,5 part of point concentration.
Keywords: Bioactivity test, antibacteria, trdisional herbs